Potential virulence factors of Nocardia seriolae AHLQ20‐01 based on whole‐genome analysis and its pathogenicity to largemouth bass (Micropterus salmoides). Issue 4 (29th December 2022) - Cao, Shoulin; Chang, Jiaojiao; Yue, Xiaozhen; Li, Jinnian; Liu, Xuelan
Abstract: Nocardia seriolae is a major causative agent of fish nocardiosis that results in serious economic losses in the aquaculture industry. However, the virulence factors and pathogenic mechanisms of the bacterium are poorly understood. Here, a new N. seriolae strain AHLQ20‐01 was isolated from the diseased Micropterus salmoides and identified by phenotypic examination combined with 16S rRNA sequencing. Subsequently, the potential virulence factors of the strain were analysed at genome level by whole‐genome sequencing. The results showed that the whole‐genome sequence derived from N. seriolae AHLQ20‐01 circular chromosome contains 8, 129, 380 bp DNA with G + C content of 68.14%, and encompasses 7650 protein‐coding genes, 114 pseudo‐genes, 3 rRNAs, 66 tRNAs and 36 non‐coding RNAs. More importantly, a total of 139 genes, which mainly involved in adhesion, invasion, resistance to oxidative and nitrosative stress, phagosome arresting, iron acquisition system, toxin production and bacterial secretion systems, were identified as core virulence‐associated genes. Furthermore, the pathogenicity of N. seriolae AHLQ20‐01 to M. salmoides was further investigated through experimental infection. It was found that the LD50 value of the strain to M. salmoides was 9.3 × 10 6  colony forming unit/fish. Histopathological examination demonstrated typical granuloma with varying sizes in the liver, head kidney, spleen and heart of the experimentally infected fish. Terminal deoxynucleotidyl transferase dUTP nick end labelling assay and 4′, 6‐diamidino‐2‐phenylindole staining showed that there were distinctly more apoptotic cells in all the tested tissues in the infection group, but not in the control group. Together, these findings provide the foundation to further explore the pathogenic mechanism of N. seriolae, which might contribute to the prevention and treatment of fish nocardiosis.